"A seething mass of rottenness": regulating food and the landscape of modern New York. (1st January 2019) - Marinaccio, Rocco
ABSTRACT: The foodways and landscape of New York were both transformed in the modern era, with new forms of regulation needed to discipline the teeming city. These transformations happened jointly, as foodways were understood as a primary and integral aspect of the city's landscape. In particular, the foodways of New York's immigrants came under increasing regulation, most notably in "The Pushcart Wars, " which characterized the immigrant and his food as a pestilential presence on the urban landscape. This joint culinary and landscape reform typifies the divergent sensibilities and constituencies that worked to fashion New York according to emergent conceptions of the modern city.